EFFECT OF CONCENTRATE SUPPLEMENTATION ON AGE AT MATURITY IN GROWING BUFFALO HEIFERS - S. A. Khanum M. Hussain; L. Jabbar; R. Kausar; A. M. Cheema; M. A. Jabbar (Journal of Animal and Plant Sciences, 2012)
Poor reproductive performance is serious limitation in exploiting the potential of buffaloes in Pakistan. Buffaloes are commonly fed poor quality forages resulting in late maturity thereby causing economical loss to the farmers. Present study was planned to observe the effect of concentrate supplementation on age of puberty of growing buffalo heifers. Eighteen Nili Ravi buffalo heifers (12±2 months old), weighing 170±8 kg were divided into two equal groups “A” and “B”. Animals in group “A” received forage alone, available in the season, and served as control. Group “B” was supplemented with a concentrate @1 kg per animal per day for first six months and then 1.5 kg per animal per day till the end of experiment along with the forage. The experiment lasted till puberty was observed in both the groups. Data regarding onset of puberty was taken by observing estrous symptoms and further confirmed through rectal palpation. A significant effect of the concentrate supplementation was noted on age at puberty. Heifers in group “A” reached to the puberty at 35.8 ±1.5 months while animals in group “B” attained the same stage at 23±0.25 months. Type of feeding strategy showed significant effect (P<0.01) on age at puberty and resulted in a decrease of 55.5% in the time required to enable the animals to breed. It appears from the results of this study that farmers could save tremendous time and resources by feeding concentrate to young growing stock for better animal production.
Keywords: Concentrate; supplementation; puberty; buffalo; forage